Numerical Performance Investigation of Parabolic Dish Solar-Assisted Cogeneration Plant Using Different Heat Transfer Fluids. (28th April 2021) - Khan, Muhammad Sajid; Abid, Muhammad; Amber, Khuram Pervez; Ali, Hafiz Muhammad; Yan, Mi; Javed, Samina
Abstract : Parabolic dish solar collectors gain higher solar to thermal conversion efficiency due to their maximum concentration ratio. The present research focuses by integrating the parabolic dish solar collector to the steam cycle producing power and rate of process heating. Pressurized water, therminol VP1, and supercritical carbon dioxide are the examined working fluids in the parabolic dish solar collector. The aim of the current research is to observe the optimal operating conditions for each heat transfer fluid by varying inlet temperature and flow rate of the working fluid in the parabolic dish solar collector, and combination of these parameters is predicted to lead to the maximum energy and exergy efficiencies of the collector. The operating parameters are varied to investigate the overall system efficiencies, work output, and process heating rate. Findings of the study declare that water is an efficient heat transfer fluid at low temperature levels, whereas therminol VP1 is effective for a higher temperature range. The integrated system efficiencies are higher at maximum flow rates and low inlet temperatures. The efficiency map of solar collector is located at the end of study, and it shows that maximum exergy efficiency gains at inlet temperature of 750 K and it is observed to be 37.75%.